2013
DOI: 10.1007/s10803-013-1808-9
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Cultural Comparison of Autistic Traits in the UK, India and Malaysia

Abstract: The disorder of autism is widely recognised throughout the world. However, the diagnostic criteria and theories of autism are based on research predominantly conducted in Western cultures. Here we compare the expression of autistic traits in a sample of neurotypical individuals from one Western culture (UK) and two Eastern cultures (India and Malaysia), using the Autism-spectrum Quotient (AQ) in order to identify possible cultural differences in the expression of autistic traits. Behaviours associated with aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
91
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(106 citation statements)
references
References 55 publications
7
91
5
Order By: Relevance
“…Wakabayashi et al (2006) noticed that their Japanese population of students tended to score higher on the AQ than students in the UK normative sample (Baron-Cohen et al, 2001). Similarly, English-speaking students in Malaysia and India attained higher AQ scores than UK students (Freeth et al, 2013). Such findings are compatible with the idea that some behaviours measured by the AQ that are symptomatic of autistic traits in the United Kingdom signify something different in Japan, India and Malaysia.…”
Section: Autism 18(1)supporting
confidence: 81%
“…Wakabayashi et al (2006) noticed that their Japanese population of students tended to score higher on the AQ than students in the UK normative sample (Baron-Cohen et al, 2001). Similarly, English-speaking students in Malaysia and India attained higher AQ scores than UK students (Freeth et al, 2013). Such findings are compatible with the idea that some behaviours measured by the AQ that are symptomatic of autistic traits in the United Kingdom signify something different in Japan, India and Malaysia.…”
Section: Autism 18(1)supporting
confidence: 81%
“…Thus, it is possible that maximizing unfamiliarity in our sample came at some cost to representativeness. Relatedly, given that endorsement of BAP features can vary based upon cultural norms (Freeth et al, 2013), the reporting of BAP traits by the ethnically diverse sample in this study may differ relative to the predominantly Caucasian samples often found in previous BAPQ studies (Sasson et al, 2013a). We also did not collect data on socioeconomic status, which potentially could impact the quality of roommate relationships.…”
Section: Discussionmentioning
confidence: 93%
“…This finding closely matches those of two previous factor analyses of the AQ in smaller adult nonclinical samples (Austin 2005;Hurst et al 2007). Other researchers, however, have reported 2, 4, or 5 factors (Stewart and Austin 2009;Hoekstra et al 2008;Kloosterman et al 2011 Freeth et al 2013b). The three-factor solution provides empirical support for three item subsets in the AQ: one subset resembling the existing Attention to Detail subscale, and two other subsets characterised, respectively, by 'sociability' and 'mentalising' items drawn from the three traditional social subscales.…”
Section: Gap Statisticmentioning
confidence: 94%